Pemanfaatan Media Sosial Sebagai Media Pemasaran Dobelcling Sabun Cuci Piring di Desa Bonto Majannang Kecamatan Sinoa - Mastaming; Syarifnur; Andi Suharman (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Humans created social media with the aim of facilitating communication between humans at any time and from any location. Social media is growing rapidly nowadays, especially in Indonesia, but many users are realizing that social media can be used for purposes other than communication, such as product marketing, online sales, and other business ventures. One of the many benefits of Instagram for marketers is that it eliminates the need for sellers or marketers to spend money, in addition to being a tool for simple and successful sales campaigns. fund their product promotion costs, allowing marketers to run as many campaigns as they want to help their products lead the market, Additionally, Instagram is getting some improvements, which I think is great. The new feature is that users who want to run product sales or promotions on Instagram can set it up. It is hoped that by educating the public about the additional benefits of social media, MSME income will increase.